การวิเคราะห์เพลงเชิดหุ่นกระบอก - วันชัย เอื้อจิตรเมศ (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The Puppet Performing song is used in the puppet show which is different from the other, since the Saw -00 player needs the ability to improvise harmonious with singing. The qualitative research methodology is used in this study: the performing method of The Puppet Performing Song both vocal and music including its coherence. The episode "Nee Nang Pee Sue Samut" from Phra Apai Manee puppet script has been taken as the case to find out the root of the puppet performing song. The result is found that the pattern of singing is derived from "Tamnong Sanoa" and some part of the "Sang-Ka-Ra" and "Thor-Ra-Nee-Rong-Hai" song. The music pattern is made from falling note of singing voice. However, both of them is based on the same notation ; Me, Fa, Sol, La, Ti, Do. There are 3 ways of ending: ending to dialogue or playing "Plang Song Chan" "Plang Rai" with Do or Sol; ending with "Plang Chud" "Samer" "La" "Roaw" with Do and ending with "Plang Oad" with Do or Sol, Concerning the root of the puppet performing, its style was derived from China. The first show was performed at Sukhothai in 1892. The well-known puppet performing is "Phra Apai Manee" of Sunthorn Phu. It is because the story is harmonized in each scenes and interesting. More of that, it shows the fact of life